PENGARUH KEPERCAYAAN, LOKASI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN BENGKEL AC MOBIL (Studi Empiris Pada Bengkel ANOMAN Kota Tegal) - Muhammad Khairul Auni, 12.05.51.0130 (Students Journal of Economic and Management, 2016)
The study of the factors that affect customer satisfaction car air conditioner repair shop (garage Anoman empirical study on Tegal). The purpose of this research is to analyze the influence of trust, location and quality of service to customer satisfaction car air conditioner repair shop (garage Anoman empirical study on Tegal). A sample of 100 respondents, the sampling method used was simple random sampling, by providing an equal opportunity for each element or member of the population to choose as a sample. Methods of data analysis using linear regression.The test results showed that (1) there are significant positive and significant correlation between trust to customer satisfaction, (2) there are significant positive and significant correlation between the location of the customer satisfaction and (3) there are significant positive and significant correlation between the quality of service to customer satisfaction. Keywords: trust, location, quality of service and customer satisfaction